2011
DOI: 10.1108/14626001111127034
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of the early growth of Belgian start‐ups

Abstract: Purpose -The purpose of this paper is to explore the heterogeneity of the initial growth trajectories adopted by young firms, using an approach similar to Delmar et al.'s analysis, in order to better understand and describe the underlying development patterns. Design/methodology/approach -The authors analyze the development during their initial years of existence of the population of all firms in Belgium which are more than three years old and have grown above micro-firm size between 1992 and 2002 (n ¼ 2,152).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The most notable is Garnsey et al ( 2006 ) whose motivation is similar to ours: “Little evidence is available on the growth paths of firms over time.” Garnsey et al ( 2006 , p. 9). Little seems to have changed since 2006 because although Garnsey et alis widely cited (considerably more than 100 times) very few of the citations actually look at growth trajectories (for four studies which do deploy similar methods to longitudinal trajectory data see Diambeidou and Gailly ( 2011 ), Hamilton ( 2012 ), Coad et al ( 2013 ) and Brenner and Schimke ( 2014 )). What most immediately distinguishes our study from Garnsey et alis the scale of the data, their study covers about 400 firms drawn from three countries (UK, Germany and the Netherlands) over periods (in some case) up to age 10.…”
Section: The Literature and Methodsmentioning
confidence: 99%
“…The most notable is Garnsey et al ( 2006 ) whose motivation is similar to ours: “Little evidence is available on the growth paths of firms over time.” Garnsey et al ( 2006 , p. 9). Little seems to have changed since 2006 because although Garnsey et alis widely cited (considerably more than 100 times) very few of the citations actually look at growth trajectories (for four studies which do deploy similar methods to longitudinal trajectory data see Diambeidou and Gailly ( 2011 ), Hamilton ( 2012 ), Coad et al ( 2013 ) and Brenner and Schimke ( 2014 )). What most immediately distinguishes our study from Garnsey et alis the scale of the data, their study covers about 400 firms drawn from three countries (UK, Germany and the Netherlands) over periods (in some case) up to age 10.…”
Section: The Literature and Methodsmentioning
confidence: 99%
“…NTBFs can represent not only a large potential pool of jobs but also a source of economic growth (Aaboen et al. , 2006; Chanut-Guieu and Tannery, 2009; Heirman and Clarysse, 2004; Saty Kouame, 2012) and innovation dissemination (Biga Diambeidou and Gailly, 2011; Cassar, 2004; Festel, 2011), which is why it seems crucial to better understand their growth trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Although these models differ regarding the number of stages and in the description of these stages, it is observed that most of them are more concerned with understanding the growth of existing companies with consolidated operations (Garnsey, 1998) to the detriment of new companies. Consequently, there is little research that has sought to understand the phenomenon of organizational development in its early stages (Churchill and Lewis, 1983; Kazanjian, 1988; Machado-da-Silva et al ., 1998), often elaborated in an overly simplified way (Diambeidou and Gailly, 2011).…”
Section: Introductionmentioning
confidence: 99%